Consider a function $f=f(x,y)$, with $df=u\ dx+v\ dy$, and we want the Legendre transformation $g=f-ux$, with $dg=df-u\ dx-x\ du=\color{red}{u\ dx}+v\ dy\color{red}{-u\ dx}-x\ du=v\ dy-x\ du$ (eliminating the dependence with $x$), then $g=g(u,y)$.

I don't understand why this works, since we have, in principle, that $g=g(x,y,u)=f(x,y)-ux$, but if $g$ doesn't depends on $x$, then $\partial g/\partial x$ must be zero: \begin{equation} \frac{\partial g}{\partial x}=\color{red}{\frac{\partial f}{\partial x}-u}-\frac{\partial^2 f}{\partial^2 x}x=-\frac{\partial^2 f}{\partial^2 x}x=0 \end{equation} (Since $\frac{\partial f}{\partial x}=u$) But why is $-\frac{\partial^2 f}{\partial^2 x}x=0$? Clearly I'm missing something here, I will appreciate your help.


1 Answer 1


The point of the Legendre transform is to switch out independent variables. You can't write $g(x,y,u)$, because $x$ and $u$ aren't independent from one another.

Another way of looking at it is that a partial derivative means taking the derivative with respect to one variable while holding all other independent variables constant. If the variables aren't independent, you're not really taking a partial derivative since you can't hold the other variables constant. Note that this means that a partial derivative with respect to one variable implies a knowledge of all other independent variables.

We must either write $g(x,y)$ or $g(u,y)$. If the former, then

$g(x,y) = f(x,y) - \frac{\partial f}{\partial x} x$


$\frac{\partial g}{\partial x} = \frac{\partial f}{\partial x} - \frac{\partial f}{\partial x} - \frac{\partial^2 f}{\partial x^2} x = -\frac{\partial^2 f}{\partial x^2} x$

and it is not zero in general.

And if we write $g(u,y)$, then $\frac{\partial g}{\partial x}$ is meaningless.

  • $\begingroup$ If $u$ and $x$ are not independent, one could write $\frac{\partial g}{\partial x}= \frac{\partial g}{\partial u}\frac{\partial u}{\partial x}$, so this is not a problem? Or otherwise said, $\frac{\partial g}{\partial x}$ still has a sense, hasn't it ? $\endgroup$ Feb 16, 2017 at 7:42
  • $\begingroup$ @FredericThomas If you do that, then $u$ isn't really an independent variable anymore. $x$ is the independent variable, and $u(x)$ is dependent on $x$, so it reduces to $g(u(x),y)=g(x,y)$. It's a bit of a semantical argument, I suppose. $\endgroup$
    – LedHead
    Feb 16, 2017 at 12:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.